Neural and Muscular Determinants of Performance Fatigability Are Independent of Work and Recovery Durations During High-Intensity Interval Exercise in Males - Chalegre Da Silva, Lucas; Da Silva, Kleber Johny; Felippe, Leandro Camati; Silva-Cavalcante, Marcos David; Henrique, Rafael dos Santos; Lima-Silva, Adriano Eduardo; Leandro, Carol Góis; Ferreira, Guilherme Assunção (Research quarterly for exercise and sport, 2025)
The present study aimed to investigate the effect of two protocols of high-intensity interval exercise (HIIE) on performance fatigability and its neural and muscular determinants. On different days, 14 healthy males performed two HIIE protocols with different work and recovery durations (matched for total duration, work and recovery intensities, and density): 1) 4 × 4 min at 90% HR peak ,180-s recovery at 70% HR peak ; and 2) 16 × 1 min at 90% HR peak , 45-s recovery at 70% HR peak . Pre- to post-HIIE reduction in maximal voluntary isometric contraction (MVIC) was used as marker of performance fatigability, while voluntary activation (VA) and potentiated quadriceps twitch force (Q tw ) as markers of the neural (i.e. central fatigue) and muscular (i.e. peripheral fatigue) determinants, respectively. In addition, pre- to post-HIIE reduction in twitch force stimulated at 100 Hz (Q tw100 ) and 10:100 Hz ratio (Q tw10 :Q tw100 ) were used as markers of high- and low-frequency performance fatigability, respectively. The MVIC, VA, T w, Q tw100 , and Q tw10 :Q tw100 ratio decreased similarly from pre- to post-HIIE in both HIIE protocols (p < .05). The rating of perceived effort, blood pH, and plasma lactate responses were similar between HIIE protocols (p > .05), but the heart rate was higher in the longer HIIE protocol (p < .05). In conclusion, performance fatigability and its neural and muscular determinants seemed to be independent of the work and recovery durations of the HIIE, at least when HIIE protocols were matched for total work duration, work and recovery intensities, and density. Further, HIIE with long work and recovery might be preferable when the intention is to stress the chronotropic response.